COVID-19: Challenges and its consequences for rural health care in India - Anant Kumar; K. Rajasekharan Nayar; Shaffi Fazaludeen Koya (Elsevier, 2020)
This commentary highlights the potential consequences of the COVID-19 pandemic for India's rural population. The rural health care system in India is not adequate or prepared to contain COVID-19 transmission, especially in many densely populated northern Indian States because of the shortage of doctors, hospital beds, and equipment. The COVID-19 pandemic creates a special challenge due to the paucity of testing services, weak surveillance system and above all poor medical care. The impacts of this pandemic, and especially the lockdown strategy, are multi-dimensional. The authors argue for the need to take immediate steps to control the spread and its aftereffects and to use this opportunity to strengthen and improve its primary health care system in rural India.